2009
DOI: 10.1080/03004430701536491
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ beliefs and practices regarding developmentally appropriate practices: a study conducted in India

Abstract: Abstract:The study assessed kindergarten teachers' beliefs, stated practices and actual practices regarding developmentally appropriate practices (DAP) in India. Forty kindergarten teachers from the urban city of Mumbai (India) participated in the study. Overall, the results indicated that teachers' beliefs were more developmentally appropriate than their stated practices or actual practices in the classroom. Further, teachers congruent in their developmentally appropriate beliefs and stated practices had clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 18 publications
5
36
0
1
Order By: Relevance
“…This finding parallels those of several prior studies regarding slippages between teachers' beliefs and practices (Erdiller & McMullen, 2003;Hegde & Cassidy;Jambunathan, 2005;Parker & Neuharth-Pritchett, 2006;Rentzou & Sakellariou, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…This finding parallels those of several prior studies regarding slippages between teachers' beliefs and practices (Erdiller & McMullen, 2003;Hegde & Cassidy;Jambunathan, 2005;Parker & Neuharth-Pritchett, 2006;Rentzou & Sakellariou, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Although there is support from research suggesting congruence between teachers' beliefs and self-reported practices (Hegde & Cassidy, 2009;Heisner & Lederberg, 2011;Leung, 2012;McCarty, Abbott-Shim, & Lambert, 2001;Mohamed & Al-Qaryouti, 2016;Rentzou & Sakellariou, 2011), it was not always the case especially when teachers' beliefs were compared with their observed classroom practices (Kwon, 2004;Varol, 2013;Wen et al, 2011;Wilcox-Herzog, 2002).…”
Section: How Do Children Learn? Beliefs and Practices Reported By Kinmentioning
confidence: 99%
“…But, this ratio is disappointing in private ECCE centres, who sometimes have 80 children in a class (Kaul et al, 2014). Hegde and Cassidy (2009) also found an average ratio of 1: 35 in the Kindergartens of Mumbai.…”
mentioning
confidence: 98%